.20x+.92*10=.65(x+10)

Simple and best practice solution for .20x+.92*10=.65(x+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .20x+.92*10=.65(x+10) equation:


Simplifying
0.20x + 0.92 * 10 = 0.65(x + 10)

Multiply 0.92 * 10
0.20x + 9.2 = 0.65(x + 10)

Reorder the terms:
9.2 + 0.20x = 0.65(x + 10)

Reorder the terms:
9.2 + 0.20x = 0.65(10 + x)
9.2 + 0.20x = (10 * 0.65 + x * 0.65)
9.2 + 0.20x = (6.5 + 0.65x)

Solving
9.2 + 0.20x = 6.5 + 0.65x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.65x' to each side of the equation.
9.2 + 0.20x + -0.65x = 6.5 + 0.65x + -0.65x

Combine like terms: 0.20x + -0.65x = -0.45x
9.2 + -0.45x = 6.5 + 0.65x + -0.65x

Combine like terms: 0.65x + -0.65x = 0.00
9.2 + -0.45x = 6.5 + 0.00
9.2 + -0.45x = 6.5

Add '-9.2' to each side of the equation.
9.2 + -9.2 + -0.45x = 6.5 + -9.2

Combine like terms: 9.2 + -9.2 = 0.0
0.0 + -0.45x = 6.5 + -9.2
-0.45x = 6.5 + -9.2

Combine like terms: 6.5 + -9.2 = -2.7
-0.45x = -2.7

Divide each side by '-0.45'.
x = 6

Simplifying
x = 6

See similar equations:

| .75*.75-6= | | 7a^2+22a+3= | | -k=(k-10) | | 2x-6=6-2x | | 36x=81 | | x+21=-8 | | 16=v(v-6) | | 9x-20+6x-5=180 | | 41=-r+32 | | 2x^2-5x-12= | | 9x(4)=81 | | 9x(4)= | | 8T=-4 | | 7x+9=6x+20 | | 3.33x=30 | | 4.5-1.5y=5.4 | | 14x-7+3y-7x-7x= | | 5(2-b)=-3(b-3) | | 9a-7=29 | | 3b^2+26b+48=0 | | 167+19x+16x=1132 | | 4x-2(x-8)=2(x+1)+5 | | 4n+2=3n | | 5x+8y=6n | | -5n=-30 | | 3x+12=9x+9 | | 3x+3/2(2x-1)=2 | | -5x-12=3x-6x | | -5=-30 | | 3q+12=9q+9 | | 23x-12=33 | | -14+6b+7-2b=1+56 |

Equations solver categories